2021
DOI: 10.1002/bit.27791
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of different biocatalyst formats for BVMO‐catalyzed cyclohexanone oxidation

Abstract: Cyclohexanone monooxygenase (CHMO), a member of the Baeyer-Villiger monooxygenase family, is a versatile biocatalyst that efficiently catalyzes the conversion of cyclic ketones to lactones. In this study, an Acidovorax-derived CHMO gene was expressed in Pseudomonas taiwanensis VLB120. Upon purification, the enzyme was characterized in vitro and shown to feature a broad substrate spectrum and up to 100% conversion in 6 h. Furthermore, we determined and compared the cyclohexanone conversion kinetics for differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 88 publications
0
4
2
Order By: Relevance
“…. This is around 4 to 5 times lower than published for the heterotrophic host Pseudomonas taiwanensis VLB120 (Schäfer et al, 2020), which showed significantly higher BVMO expression levels (Bretschneider et al, 2021a) and features a highly active energy and redox metabolism based on organic acids and sugars (Volmer et al, 2014). It is however noteworthy that the BVMO exhibited a much higher in vivo activity in Syn6803 than in P. taiwanensis, that is, a 4.6 to 11 times higher k cat (6.9-17.6 s −1 vs. 1.5 s −1 (Bretschneider et al, 2021a)).…”
Section: Photosynthesis-driven Bvmo Catalysis Is Hampered By Reactant Inhibition Rather Than Host Metabolismcontrasting
confidence: 55%
See 2 more Smart Citations
“…. This is around 4 to 5 times lower than published for the heterotrophic host Pseudomonas taiwanensis VLB120 (Schäfer et al, 2020), which showed significantly higher BVMO expression levels (Bretschneider et al, 2021a) and features a highly active energy and redox metabolism based on organic acids and sugars (Volmer et al, 2014). It is however noteworthy that the BVMO exhibited a much higher in vivo activity in Syn6803 than in P. taiwanensis, that is, a 4.6 to 11 times higher k cat (6.9-17.6 s −1 vs. 1.5 s −1 (Bretschneider et al, 2021a)).…”
Section: Photosynthesis-driven Bvmo Catalysis Is Hampered By Reactant Inhibition Rather Than Host Metabolismcontrasting
confidence: 55%
“…This is around 4 to 5 times lower than published for the heterotrophic host Pseudomonas taiwanensis VLB120 (Schäfer et al, 2020), which showed significantly higher BVMO expression levels (Bretschneider et al, 2021a) and features a highly active energy and redox metabolism based on organic acids and sugars (Volmer et al, 2014). It is however noteworthy that the BVMO exhibited a much higher in vivo activity in Syn6803 than in P. taiwanensis, that is, a 4.6 to 11 times higher k cat (6.9-17.6 s −1 vs. 1.5 s −1 (Bretschneider et al, 2021a)). It should be noted that BVMO catalysis in Syn6803 appeared not to be limited by the metabolic capacity to supply reduction equivalents as the photoproduction of NADPH in Syn6803 is in the range of 9-18 U mg Chl a (Kauny and Setif, 2014), which translates to 106-212 U g CDW −1 .…”
Section: Photosynthesis-driven Bvmo Catalysis Is Hampered By Reactant Inhibition Rather Than Host Metabolismcontrasting
confidence: 55%
See 1 more Smart Citation
“…Crude cell extracts were obtained as previously described, [9b] but with extended centrifugation for 30 min after cell disruption. Enzyme activity was determined based on the decrease in NAD(P)H absorption at 340 nm with a Cary Bio 300 UV‐visible spectrophotometer (Varian, Palo Alto, USA) following a described procedure: [37] Assay mixtures of 2 ml total volume in a screw capped cuvette contained 200 μM NAD(P)H and 50–100 μl crude cell extract (0.1–0.3 mg protein) in 100 mM KPi buffer. Assays were initiated by adding 2.5 μl pure cyclohexane and were performed for at least 2 min.…”
Section: Methodsmentioning
confidence: 99%
“…Depending on the reaction(s) to be catalyzed, resting cells can be easier to handle and reusable but often suffer from poor stability (Julsing et al, 2012;Zhang et al, 2012). Recently, mixed-species concepts have been used to produce the monomer adipic acid, 6-aminohexanoic acid, or 1,6-hexanediol from cyclohexane (Wang et al, 2020;Zhang et al, 2020;Bretschneider et al, 2021).…”
Section: Introductionmentioning
confidence: 99%